Sun bears use 14‐year‐old previously logged forest more than primary forest in Sabah, Malaysia. Issue 10 (14th October 2021) - Hwang, Mei‐Hsiu; Ditmer, Mark A.; Teo, Shu‐De; Wong, Siew Te; Garshelis, David L.
Abstract: Sun bears ( Helarctos malayanus ), arguably the least‐known bear species, are endemic to Southeast Asia and are believed to be in rapid decline due to forest loss and poaching, which are severe threats across this region. It has been asserted that, unlike other forest‐dependent, omnivorous bears, sun bears are especially sensitive to changes in forest composition and canopy closure because they often feed on fruits in the canopy. We investigated habitat use of sun bears in a region of Sabah, Malaysian Borneo, containing primary forest adjacent to a 14‐yr‐old selectively logged forest. We used strip transects to quantify trees that sun bears climbed to forage or rest; these were easily recognized by distinctive claw marks. We found 1.8× the density of bear‐climbed trees in the logged vs. the primary forest. Dead wood, a home for various insects eaten by sun bears, was more common in logged forests. Except during masting years, when fruits are exceptionally abundant in this area, sun bears commonly consume termites and bees, both of which were more common in the logged forest and had a positive effect on sun bear presence. Sun bear presence was also positively associated with canopy closure, which on average was higher in primary forest, but some portions of logged forest had very high canopy cover. The logged forest had higher vegetative greenness, which up to a point was attractive to bears, but very high greenness, likely indicative of thick underbrush, appeared to be less attractive. These results indicate that previously logged areas can be valuable habitats for sun bears, providing rich supplies of food––both fruits and insects. A number of recent biodiversity surveys using camera traps have also shown high use of logged areas by sun bears, but here we connected this use to food resources. Conservation of this species is better served by appreciating its omnivorous diet and adaptiveness to varying habitats and thus recognizing the importance of preventing logged areas from deteriorating into agriculture. We warn against focusing only on saving primary forests, and predicting declines of this species from forest cutting, without considering forest regeneration.